2016
DOI: 10.1016/j.xphs.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Food on the Intraluminal Behavior of Abiraterone Acetate in Man

Abstract: To relate the reported positive effect of food on the oral bioavailability of abiraterone to the intraluminal behavior of abiraterone acetate, an in vivo experiment was performed, in which duodenal fluids and plasma samples were collected from healthy volunteers after the administration of abiraterone acetate in fasted and postprandial conditions. The plasma concentration-time profiles confirmed the positive food effect. Nevertheless, intraduodenal concentrations of abiraterone acetate and abiraterone did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…They found that food effect was a statistically significant covariate on oral clearance for abiraterone [8]. Other studies have found substantial food effect in healthy subjects when AA was given following a meal, with plasma abiraterone exposure increasing by 2.9-to 10-fold [9,10,12]. For example, Chi et al reported that in healthy subjects administered the OAA formulation, the area under the plasma concentration-time curve (AUC) and maximum measured plasma concentration (C max ) of abiraterone, the active metabolite of AA, increased by 10-and 17-fold, respectively, when given shortly after a high-fat meal relative to the fasted state [10].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…They found that food effect was a statistically significant covariate on oral clearance for abiraterone [8]. Other studies have found substantial food effect in healthy subjects when AA was given following a meal, with plasma abiraterone exposure increasing by 2.9-to 10-fold [9,10,12]. For example, Chi et al reported that in healthy subjects administered the OAA formulation, the area under the plasma concentration-time curve (AUC) and maximum measured plasma concentration (C max ) of abiraterone, the active metabolite of AA, increased by 10-and 17-fold, respectively, when given shortly after a high-fat meal relative to the fasted state [10].…”
Section: Introductionmentioning
confidence: 94%
“…The AA tablets should be swallowed whole with water and should not be crushed or chewed [7]. Several studies have investigated the effect of food on AA absorption and bioavailability [8][9][10][11][12] and established that consumption of a high-fat meal before administration of the originator AA (OAA) formulation markedly increases abiraterone absorption [9,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal cause of positive food effects is the increase in dissolution and solubilisation of poorly water‐soluble drugs (PWSD) in the fed state. The release of bile salts and the presence of exogenous solubilising species, such as ingested lipids and their digestion products serve to enhance solubilising capacity of gastrointestinal fluid . For drugs which are dissolution rate, rather than solubility limited, the increased gastric residence time also can improve bioavailability, while the increase in gastric pH may result in improved solubility and dissolution of weak acids.…”
Section: Food Effects; Causes and Clinical Consequencesmentioning
confidence: 99%
“…For BCS class IV drugs, the impact of extensive luminal solubilization in the fed state is even less straightforward as in this case transport through the mucosa may also be influenced by changes in the membrane fluidization (which may be induced by the interaction with surfactants) or the activity of membrane transport carriers . Geboers et al . observed a positive food effect on IR tablets containing 250 mg abiraterone acetate (Zytiga ® ), a BCS class IV drug, after administration with a liquid meal (Ensure ® plus).…”
Section: The Role Of Drug and Formulation On The Occurrence Of Food Ementioning
confidence: 99%